2011
DOI: 10.1111/j.1757-7861.2011.00144.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of ultrasound in the treatment of osteoarthritis of the knee

Abstract: Ultrasound treatment significantly alleviates joint symptoms, relieving joint swelling, increasing joint mobility and reducing inflammation, in osteoarthritis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 19 publications
1
30
0
2
Order By: Relevance
“…This relatively new treatment modality has been shown to promote the repair of full-thickness tears in articular cartilage. Specifically, it has been found that the pressure waves induce stromal cell and chondrocyte proliferation in addition to mesenchymal stem cell differentiation at the lesion site 7 , 8 , 9 ) . However, the therapeutic effects of US are more pronounced in the joint spaces, such as the knee joints, because synovial fluid has high water content 10 ) .…”
Section: Introductionmentioning
confidence: 99%
“…This relatively new treatment modality has been shown to promote the repair of full-thickness tears in articular cartilage. Specifically, it has been found that the pressure waves induce stromal cell and chondrocyte proliferation in addition to mesenchymal stem cell differentiation at the lesion site 7 , 8 , 9 ) . However, the therapeutic effects of US are more pronounced in the joint spaces, such as the knee joints, because synovial fluid has high water content 10 ) .…”
Section: Introductionmentioning
confidence: 99%
“…7 Recently, pulsed US applied using a low intensity (<1 W/cm 2 ) and low frequency (<1 MHZ) had positive effect on patients with Knee OA, including alleviating joint pain, relieving swelling, increasing joint mobility and reducing inflammation. 8 Ozgonelel et al conducted a randomized double blind, placebo controlled study the effects of therapeutic pulsed ultrasound treatment and placebo treatment results showed a statistically significant improvement in pain, difference in recovery in the pulsed ultrasound group in terms of VAS score. 9 In our study, found that a significant improvement in reduce effusion volume, pain reduction, swelling, active range of motion in (group I) compared with patients in the control (group II).…”
Section: Resultsmentioning
confidence: 99%
“…Yang ve ark. 87 hasta ile yaptıkları çalışmada, US tedavisinin anlamlı şekilde eklem semptomlarını azalttığını, eklem effüzyonunu azalttığını, eklem mobilitesini arttırdığını ve diz inflamasyonunu azalttığını göstermişlerdir (21). Aynı şekilde, Özgönönel ve ark.…”
Section: Discussionunclassified